Development of "Sit and Reach" Flexometer Using Infra-Red - Dzihan Khilmi Ayu Firdausi; Muhammad E. M. Simbolon (Journal Physical Education, Health and Recreation, 2020)
This research generally aims to develop a "sit and reach test" flexometer that can measure the flexibility of a person's body. Specifically, this research aims to: (1) replace conventional measurement of flexibility, because this measuring instrument will work electronically; (2) developing a flexometer that works electronically using infrared so that it is processed by a microcontroller so that the test results in the form of distance are automatically classified (3) developing a flexometer that is more modern, practical, effective and efficient. This research uses a product development (research & development) approach that is consists of several steps, namely observation, planning and design, experimentation and testing, and analysis. Products were tested for validity using the construct validity and product reliability methods with the retest method. Based on data analysis, the validity value of the flexometer auto compared to the conventional measurement of flexibility is 0.645098. Based on the analysis of the reliability test data obtained r11 = 0.988> rt = 0.312. It can be concluded that the automation felxometer uses valid and reliable infrared to be used in measuring the flexibility of the body in the sit and reach test.